Astrocyte glutathione maintains endothelial barrier stability - Sheng-Fu Huang (Redox Biology, 2020)
Blood-brain barrier (BBB) impairment clearly accelerates brain disease progression. As ways to prevent injury-induced barrier dysfunction remain elusive, better understanding of how BBB cells interact and modulate barrier integrity is needed. Our metabolomic profiling study showed that cell-specific adaptation to injury correlates well with metabolic reprogramming at the BBB. In particular we noted that primary astrocytes (AC) contain comparatively high levels of glutathione (GSH)-related metabolites compared to primary endothelial cells (EC). Injury significantly disturbed redox balance in EC but not AC motivating us to assess 1) whether an AC-EC GSH shuttle supports barrier stability and 2) the impact of GSH on EC function. Using an isotopic labeling/tracking approach combined with Time-of-Flight Mass Spectrometry (TOF-MS) we prove that AC constantly shuttle GSH to EC even under resting conditions - a flux accelerated by injury conditions in vitro. In correlation, co-culture studies revealed that blocking AC GSH generation and secretion via siRNA-mediated γ-glutamyl cysteine ligase (GCL) knockdown significantly compromises EC barrier integrity. Using different GSH donors, we further show that exogenous GSH supplementation improves barrier function by maintaining organization of tight junction proteins and preventing injury-induced tight junction phosphorylation. Thus the AC GSH shuttle is key for maintaining EC redox homeostasis and BBB stability suggesting GSH supplementation could improve recovery after brain injury.